State Long-Term Care Ombudsmen's Perceptions of Their Program's Disaster Preparedness Roles and Readiness. (December 2013) - Nelson, H. Wayne; Agley, Daniel; Netting, F. Ellen; Borders, Kevin W.; Huber, Ruth
A telephone survey of 43 state long-term care ombudsmen (LTCO) assessed their familiarity with relevant long-term care disaster resources, their provision of disaster aids and training to staff, and their perceived preparedness to lead their programs during public crises. Thirty-four directors (78%) reported being fairly well to fully prepared to support their local programs during public emergencies. However, ANOVAs showed that the 27 disaster experienced ombudsmen felt no better prepared to help their local paid and volunteer staff deal with public emergencies than disaster inexperienced ombudsmen. Those directly involved with emergency planners felt better prepared to help their substate staff to know where to start helping residents during a public crisis than ombudsmen who had no involvement with disaster planners. Familiarity with the Centers for Medicare and Medicaid Services Emergency Planning Checklist for LTC Ombudsmen (2007) was strongly associated with the ombudsmen's familiarity with emergency resources and regulations.